Peran Kesiapan Organisasi Sebagai Moderator Dalam Pengaruh Transformasi Digital, Kompetensi SDM, Dan Kepemimpinan Transformasional Terhadap Efisiensi Operasional Pada PT Asuransi Sinar Mas - Irawan, Puthut Nuke; Subarjo Joyosumarto; Enny Haryanti; Edi Komara (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to analyze the effect of digital transformation, human resource (HR) competence, and transformational leadership on operational efficiency at PT Asuransi Sinar Mas, with organizational readiness as a moderating variable. The research is motivated by the phenomenon of the productivity paradox, where high digital investment has not been followed by optimal efficiency. A quantitative approach was employed using a survey method involving 246 employees in the DKI Jakarta region. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results indicate that digital transformation and HR competence have a positive and significant effect on operational efficiency, while transformational leadership does not show a significant direct influence. Furthermore, organizational readiness significantly moderates the relationship between HR competence and operational efficiency. However, it was found to significantly weaken (negative moderation) the impact of digital transformation on operational efficiency, suggesting that structural rigidity may hinder technological benefits. In contrast, organizational readiness does not significantly moderate the relationship between transformational leadership and operational efficiency. These findings imply that the success of digital transformation is not solely determined by technology adoption, but also by the harmonization of organizational readiness and HR capabilities. This study provides managerial insights for insurance companies to prioritize human-centric development and business process re-engineering to eliminate organizational barriers in digital adoption.